Integrating the 2030 Agenda at the municipal level: Multilevel pressures and institutional shift. (June 2021) - Annesi, Nora; Battaglia, Massimo; Gragnani, Patrizia; Iraldo, Fabio
Abstract: Purpose: The integration of environmental principles into the public decision-making process has been a public policy priority during the last 30 years. However, 5 years after the development of the UN 2030 Agenda, such integration is still at an initial stage, with no significant actions having been implemented either at the national or local level. This paper presents the experience of the municipality of Lucca, which found itself under pressure from the Fridays For Future movement (FFF) that requested the city take urgent action on climate change. In the framework of this initiative, the study aims to answer the following question: based on pressures emerging from social and institutional context, how to institutionalize the integration of sustainability principles and SDGs at the municipal level? Study design/methodological approach: This study has been developed as research practice. In an attempt to enrich the public decision-making approach with the systematic integration of environmental and sustainable principles, the method, the results provided, and the knowledge created are linked to the action research (AR) framework. Findings: Within the institutional theory framework and viewing the city as a viable system, the study makes three distinct contributions. First, from a theoretical point of view, the case analyzes the impact of an activist group using its relative power. Second, the study proposes a model for the systematic integration of sustainability principles with municipal practices as a tool of institutional change. Third, from an empirical standpoint, it identifies the UN 2030 Agenda as a governance tool of a municipality. Originality: The study, for the first time, analyzes the application of a global policy at the local level, thanks to the pressure of a local group of organized citizens that has a global impact. Limitation: The primary limitation of the study is the lack of comparison with other contexts and municipalities. Limitations in the applicability of the designed model to other contexts are linked to the nature of the city in which it has been developed. The model is the result of action-research and in this sense, it is necessary and desirable that future studies embrace the application of this particular research method to modify and improve it. Highlights: The 2030 Agenda represents a tool for the effective transposition of sustainability policies from a global to a local level. Public governance and decisional processes can be reconfigured by including sustainability principles. Institutional and viable system theory can transform administrations into coherent entities to tackle sustainability. The crisis moment triggered by the FFF became an opportunity to introduce and accelerate an institutional change.